Pengaruh Leverage, Arus kas Operasi, Ukuran Perusahaan dan Fixed Asset Intensity terhadap Keputusan Revaluasi Aset tetap (Studi Empiris pada Bank Umum yang Terdaftar di BEI Periode 2012 s.d. 2016) - Sudradjat, Sudrajat; Ahmar, Nurmala; Mulyadi, JMV (Institut Bisnis dan Informatika Kesatuan, 2017)
Implementation of financial statement preparation for public companies in Indonesia has shifted from Generally Accepted Accounting Principles (GAAP) to the International Financial Reporting Standards (IFRS) starting in 2012. GAAP practices emphasize to users to find the best terms for a transaction, while IFRS emphasizes principles of fair value in the presentation of financial statements. The Financial Position Report which has adopted IFRS requires that the fixed assets be presented at fair value, so that the financial statements presented to external parties reflect the current value of fixed assets owned by the company. This study aims to investigate the effect of leverage, operating cash flow, firm size and fixed asset intensity to the decision of commercial banks to conduct a revaluation. Commercial Bank that became the object of research is a commercial bank listed on the BEI with observation period starting in 2012 - 2016. Independent variable are leverage, operating cash flow, firm size and fixed asset intensity. Testing on the research model using Hosmer & Lemeshow Test, Omnibus, Nagelker R Square. While testing the hypothesis using Logistic Regression Test. The results of the analysis in hypotesis testing showed that leverage, firm size and fixed asset intensity significantly influence the decision of commercial banks to conduct a revaluation. While operating cash flow has no effect on the decision of commercial banks to conduct a revaluation.